Chenodeoxycholic acid triggers gastric mucosal injury by inducing apoptosis and FXR activation - Shuaijun Peng; Ruiqin Sun; Hui Liu; Baoying Wang; Yucheng Li (PLoS ONE, 2025)
Gastric mucosal injury can lead to significant gastrointestinal disorders, including inflammation, ulcers, and intestinal metaplasia in severe cases. Although bile acids are known contributors to mucosal damage due to their acidity, the role of chenodeoxycholic acid (CDCA), a primary bile acid, in gastric mucosal injury remains unclear. This study investigates the role of CDCA in inducing gastric mucosal injury and its underlying mechanisms, with a focus on apoptosis and FXR activation, to identify potential therapeutic targets. Mice were administered varying doses of CDCA to evaluate changes in body weight, food intake, and gastric mucosal pathology using hematoxylin-eosin (HE) and alcian blue-periodic acid-Schiff (AB-PAS) staining. Expression levels of apoptosis-related genes (BAX, BCL-2) and the intestinal metaplasia marker gene (CDX2) were analyzed via RT-PCR and Western blotting (WB). GES-1 cells were treated with different CDCA concentrations to assess cell viability via the CCK-8 assay. Apoptosis rates were measured using flow cytometry, and FXR inhibitors were applied to examine their impact on CDCA-induced effects. CDCA administration in mice resulted in weight loss, reduced food and water intake, gastric epithelial shedding, and intestinal metaplasia. CDCA exposure upregulated Bax and CDX2 expression, while reducing BCL-2 levels. In vitro, CDCA inhibited GES-1 cell viability and increased apoptosis rates, effects that were reversed by FXR inhibition. CDCA induces gastric mucosal injury through apoptosis and FXR activation. These findings provide insights into the mechanisms of bile acid-mediated mucosal damage and highlight FXR as a potential therapeutic target for gastric mucosal disorders.